Gambaran Patologi Anatomi dan Histopatologi Organ Visceral Kambing Kacang (Capra aegagrus hircus) Yang Terinfeksi Sistiserkus - Teklania Nggio Ringgi; Yeremia Y Sitompul; Filphin A Amalo; Aji Winarso (Jurnal Veteriner Nusantara, 2023)
The demand for kacang goat (Capra aegagrus hircus)in Kupang City is very high in the local market, especially before the sacrificial festival. Although the goat population growth is high, there are several reasons that cause low productivity, namely parasitic infection.worms Taenia infect carnivores (as well as humans) as the definitive host and involve an intermediate host which will develop into a cysticercus. The purpose of this study was to determine the anatomical pathology and histopathology of the visceral organs of kacang goats infected with cysticercus. This study used 6 samples of visceral organs of kacang goats consisting of 4 liver organs, 1 rumen organ and 1 colon organ from 6 kacang goats infected with cysticercus, in Pasir Panjang Village, Kupang City. Macroscopic observations, tissue fixation in 10% formalin, tissue processing and HE staining were carried out. The results of the study on liver organs infected with cysticerci showed pathological changes in the form of fibrosis, while in the rumen and colon only cysticerci were formed. Histopathological changes in the liver organs of kacang goat infected with cysticercus in the form of mononuclear and polymorphonuclear inflammatory cell infiltration, necrosis, congestion, hemorrhage, hydropic degeneration, widening of sinusoids and fibrous tissue. Meanwhile, changes that occur in the rumen and colon organs are in the form of infiltration of mild inflammatory cells.